The Importance of Gamification in Education - Kamalova Gulzada (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This article presents a systematic review of the literature on the importance of gamification in education. Gamification, defined as the application of game-design elements and principles in non-game contexts, has gained significant traction in the educational field. This article examines the key aspects of gamification's impact on the learning process, including student motivation, engagement, academic performance, and skill development. Based on an analysis of current research, both the positive effects and potential challenges of implementing gamification in education are identified.